2008
DOI: 10.1002/pmic.200701034
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential serum markers for nasopharyngeal carcinoma from a xenografted mouse model using Cy‐dye labeling combined with three‐dimensional fractionation

Abstract: Nasopharyngeal carcinoma (NPC), one of the most common cancers in Southeast Asia, is commonly diagnosed late due to its deep location and vague symptoms. To identify biomarkers for improving NPC diagnosis, we established a proteomic platform for detecting aberrant serum proteins in nude mice bearing NPC xenografts. We first removed the three most abundant proteins from serum samples of tumor-bearing and control mice, and then labeled the samples with different fluorescent cyanine (Cy) dyes. The labeled serum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…S2), and the SWATH results could pass the manual spectra inspection; 2) Wu et al . previously reported that CA2 was up-regulated in the serum of NPC xenograft mice29; and 3) the CA2’s diagnostic power had not been reported in the NPC field.…”
Section: Resultsmentioning
confidence: 97%
“…S2), and the SWATH results could pass the manual spectra inspection; 2) Wu et al . previously reported that CA2 was up-regulated in the serum of NPC xenograft mice29; and 3) the CA2’s diagnostic power had not been reported in the NPC field.…”
Section: Resultsmentioning
confidence: 97%
“…Early indications were that parent ion intensities from MALDI analysis were in agreement with those of LC-ESI-MS (Griffin et al, 2001) and that parent and fragment ion intensities between separate runs of normal and diseased samples were consistent with Western blots or ELISA analysis of the same sample fractions (Marshall et al, 2003;Reynolds et al, 2003;Zhang et al, 2004;Malik et al, 2005;Yokoi et al, 2005;Yang et al, 2006;Haqqani et al, 2007;Morgan et al, 2007;Wilson et al, 2007;Barba de la Rosa et al, 2008;Gramolini et al, 2008;Hammerer-Lercher et al, 2008;Hao et al, 2008;Kolialexi et al, 2008;Kulasingam et al, 2008;Luque-Garcia et al, 2008;Marchi et al, 2008;Nicol et al, 2008;Plavina et al, 2008;Reichel, 2008;Xing et al, 2008;Wu et al, 2008a;Wang et al, 2008b;Zhao et al, 2008b;Domae et al, 2009;Fortin et al, 2009). Hence, where there is doubt regarding the best fit of the data, a second method such as accurate parent mass, targeted MS/MS, MRM, synthetic chromatography and spectrometry standards or immunological confirmation may be employed (Marshall et al, 2003;Zhang et al, 2004;Malik et al, 2005;Yokoi et al, 2005;Gao et al, 2005a;Haqqani et al, 2007;Plavina et al, 2007;Sardana,...…”
Section: Agreement Between Biochemical and Mass Spectral Methodsmentioning
confidence: 92%
“…Allelic variation may also be established with electrophoresis (Csaszar et al, 2001). The combination of column or other pre-fractionations prior to SDS-PAGE remains a popular approach (Wu et al, 2008a) that may yield thousands of proteins (Sennels et al, 2007). Electrophoresis of intact proteins after depletion and multi-dimensional separation permitted the detection of low abundance proteins from serum .…”
Section: E One-dimensional Poly Acrylamide Gel Electrophoresis (1d Pmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the progress of these studies has been hampered by the complex nature of serum/plasma samples and the large dynamic range between the concentrations of different proteins (14). As cancer biomarkers are likely to be present in low amounts in blood samples, the direct isolation of these markers from plasma and serum samples requires a labor-intensive process involving the depletion of abundant proteins and extensive protein fractionation prior to mass spectrometric analysis (15)(16)(17)(18). Alternatively, the secretome, or group of proteins secreted by cancer cells (19), can be analyzed to identify circulating molecules present at elevated levels in serum or plasma samples from cancer patients.…”
mentioning
confidence: 99%